“Round numbers are always false” – More EMIC (culturally contingent) than ETIC (universal)? Is national culture a defining facet of leadership in the defence and security sector? - Forgrave, Martyn W. (Cranfield University, 2021)
Leadership as a function in human groups is found in all corners of the world and can be traced by as far as the start of recorded history. Plato (428/429 BCE 348/347 BCE) was the first to write about the general attributes that determine leadership. This quest to identify traits that predict effective leadership continues to this day. Since the mid-twentieth century, scholarly attempts have been made to establish a universal theory of leadership that transcends cultural boundaries. Although the search for a definitive universal model has so far proved inconclusive, cross-cultural research continues to be focussed on determining whether aspects of leadership and leadership theory are “universal” (etic) or culturally contingent (emic) (i.e., unique to culture). The GLOBE project (2004), the most expansive and significant cross-cultural study to date, found that although leadership is culturally contingent, universal attributes of leadership exist. Although cross-cultural research on leadership has exploded in importance in the last twenty-five years or so, its existence is almost absent in all U.K. defence policy and doctrinal publications. Yet, the MOD’s policy position is to be “international by design” (MOD, 2018) and the recently published Integrated Review of Security, Defence, Development and Foreign Policy (MOD, 2021) signposts deepening defence and security international engagement over the coming decade. A critical review was conducted of selected academic and military literature on leadership, culture, and cross-cultural leadership. A research methodology was designed and developed to focus on a predominantly quantitative approach. This was driven primarily by the research question. However, this was offset by open questions to provide a qualitative element. Therefore, a mixed methods approach was used in this thesis. The research investigated prototypical leadership in sixteen countries across four continents. The cross-cultural research, focussed on equivalence and comparability, was carried out using seven regions as independent variables. The selection of the “middle manager” strata of leadership (Brigadier General to Major) provided functional equivalence. The questionnaire sample size was 1067. The survey included closed and open ended questions which were translated into Arabic, Georgian, Ukrainian, Burmese, Spanish and Korean. The main findings included the identification of twenty-five essential leader attributes that were considered essential across seven regions in the defence and security sector. The thesis failed to reject the null hypothesis that ‘effective leadership attributes, skills and traits in the defence and security sector are culturally contingent across countries and regions.’ The identification of a core of essential military leader attributes, demonstrating “partial universality”, was offset by wider findings that showed leadership in the defence and security sector to be culturally contingent across the sixteen countries. A cross-cultural prototypical military leadership model was constructed to provide a systematic and structured understanding of cross-cultural leadership and a means of cross-cultural comparability. The contextual model is based on seven leader dimensions encapsulating ‘personality and self’, ‘motives’, ‘cognitive capacities and skills’, ‘emotional capacities and social skills’, ‘integrity and moral character’, ‘team skills’ and ‘task skills’. Recognising that culture and leadership have a symbiotic relationship, in which one cannot exist without the other (Ayman & Korabik, 2010), the leadership construct is bound by culture at the micro (individual), meso (organisational) and macro (national) levels. Finally, the research makes a discrete contribution towards an etymological study of “leader” and “leadership” across cultures. An understanding of the etymology assists with the way we think about, study and enact leadership (Case et al., 2011). The findings show that a variance in semantics is indicative of cultural contingency. Notwithstanding this, there is sufficient similarity to permit a route scheme of meaning. Recommendations are made to investigate an expeditionary version of the GLOBE study (2004) questionnaire where data can be collected and collated efficaciously to contribute to the project from an organisational perspective. Further research should examine how the GLOBE study’s six global leadership dimensions can be applied to the defence and security sector. Follow-on work should also be carried out to understand the behavioural manifestations of identified attributes in the defence and security sector. This would make an important contribution to interoperability workstreams and multinational activities with allies and partners. A formal review is recommended to address the cross cultural deficit in U.K. Defence and that the doctrinal gap is closed in the re-write of Leadership in Defence (2004). More broadly, a more coherent approach should be taken between the defence proponents of leadership and culture. Recognising both the complexity and importance of cross-cultural leadership, the Ministry of Defence may wish to take forward the idea of trans-cultural alliances between leadership schools to promote information exchange and achieve a better understanding of indigenous military leadership constructs. Finally, a cross-cultural study into the leadership gender gap in the defence and security sector would provide a valuable research topic. This would advance the status of women in professional military forces as culture has been found to be an obstacle to gender egalitarianism, participation, and advancement in armed forces around the globe.
© Cranfield University 2019. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Leadership; Culture; Military security; Defnece and security UK